Managing risk in complex adult professional learning: the facilitator's role. Issue 2 (15th March 2017) - Ince, Amanda
Abstract : This article reports on the recognition and management of risk within the context of an intensive literacy intervention professional development programme, designed to enable expert literacy teachers become teacher-educators. The article suggests a conceptual model for recognising risk within professional learning opportunities and skills for facilitators. Data were generated from digital audio recordings of professional development sessions and semi-structured interviews. Data were analysed using a grounded theory approach. Data analysis revealed attributes for facilitators which enabled or determined their ability to manage risk. Extracts from transcripts illustrate the nature of risk and participant perception. Implications for facilitators of professional learning to support learners through their transformative learning journey are discussed.